2005
DOI: 10.1007/978-3-540-31984-9_9
|View full text |Cite
|
Sign up to set email alerts
|

Using Scenarios to Predict the Reliability of Concurrent Component-Based Software Systems

Abstract: Abstract. Scenarios are a popular means for capturing behavioural requirements of software systems early in the lifecycle. Scenarios show how components interact to provide system level functionality. If component reliability information is available, scenarios can be used to perform early system reliability assessment. In this paper we present a novel automated approach for predicting software system reliability. The approach involves extending a scenario specification to model (1) the probability of componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 22 publications
0
75
0
9
Order By: Relevance
“…They have shown that RADL allows software architects to predict component reliability through compositional analysis of usage profiles and of environment component reliability [5] Genaina Rodrigues, David Rodenblum presents a novel automatic approach for predicting software system reliability. This approach involves the probability of component failure and Scenario transition probabilities derived from an operational profile [6]. L Thomas Zimmermann, Nachiappan Nagappan shows how to use the complexity of a subsystem dependency graph to predict the number of failures at statistically significant levels [7].…”
Section: Related Workmentioning
confidence: 99%
“…They have shown that RADL allows software architects to predict component reliability through compositional analysis of usage profiles and of environment component reliability [5] Genaina Rodrigues, David Rodenblum presents a novel automatic approach for predicting software system reliability. This approach involves the probability of component failure and Scenario transition probabilities derived from an operational profile [6]. L Thomas Zimmermann, Nachiappan Nagappan shows how to use the complexity of a subsystem dependency graph to predict the number of failures at statistically significant levels [7].…”
Section: Related Workmentioning
confidence: 99%
“…Most promising reliability evaluation methods, i.e. the methods from Cortellessa et al [17], Rodrigues et al [18], Yacoub et al [19], Reussneer et al [20], and Grassi [21] have been compared in [22] from the viewpoint of software architecture. The Reliability and Availability Prediction (RAP) method [23] and the Quality Requirements of a software Family (QRF) method [24] highlight how quality requirements have to be defined, represented and transformed to architectural models.…”
Section: Motivationsmentioning
confidence: 99%
“…In previous work, we presented a scenario-based approach to reliability prediction of concurrent systems by synthesizing architecture model from scenario specification [8]. The contribution of this paper is to show how our reliability prediction technique can provide guidance towards enhancing the reliability of the software system.…”
Section: Introductionmentioning
confidence: 99%
“…The method is based on the annotation of a scenario specification with probabilistic properties and the use of a probabilistic labelled transition system (LTS) synthesised from the scenario specification for the software reliability prediction. We refer the reader to our earlier paper for a more detailed explanation of our model [8].…”
Section: Introductionmentioning
confidence: 99%